KNOWLEDGE AND APPLICABILITY OF BIOETHICS: SAN MARCOS UNIVERSITY- PERU AND CULAGOS / GUADALAJARA - MEXICO - Gutiérrez Huby, Ana María (2015)
This article is about the knowledge and applicability of bioethics at the University Centers of San Marcos and Los Lagos- CULAGOS/University of Guadalajara. This is a basic descriptive applicative research. The goal is to develop in students, bioethical reasoning for their improvement and decision making when facing ethical conflicts that may arise. It also determines methods and strategies to incorporate this discipline in the curriculum and include it in the integral formation of future business managers. Furthermore, we state that at the institutional level in both centers, what is stated in their respective missions does not harmonize with the implementation of the student profile. It is evidenced, the institutional commitment that the university has as a public entity, which implies working from the perspective of rights, the defense of education for life and society, recognition of civil rights, protection of all forms of life and the environment; also the invol-vement of bioethics for the integral formation of the human being generating knowledge with social sense. We conclude with the need to incorporate this disci-pline to business education for the establishment of principles to guide the formation of business students.